Royal Navy: evolução e superioridadedo poder naval britânico na era dos navios a vela - Rodney Alfredo Pinto Lisboa (Navigator)
Geographically located between the Atlantic Ocean, English Channel, the Irish Sea and the North Sea, the British Isles have always been susceptible to any foreign threats. Based on an expansionist philosophy of power projection that astute diplomacy combined with the efficiency of the military instrument, the British developed a Navy able to compete and overcome other powers in the quest for control of sea lanes of commerce and hegemony in the oceans. Through the experiences gained in the course of many decisive battles, the Royal Navy imposed upon their opponents in different naval conflicts fought between the 16th and 19th centuries, emerging at the end of the Napoleonic Wars (1799-1815) as the greatest naval power in the age of sailing ships.